Anxiety Of Amanda In Johanna Lindsey's A Man To Call My Own Novel (2003): A Psychoanalytic Approach - Kharisma, Gusti Dilla, Drs. Abdillah Nugroho, M. Hum, Siti Fatimah, S. Pd, M. Hum (2014)
The problem of this study is to reveal how the anxiety is in major character. The objective of this study is to analyze the novel based on the structural elements and to analyze the major character in A Man to Call My Own novel based on a psychoanalytic Approach. This study is a literature. The type of this research is qualitative research. The object of this study is Johanna Lindsey's A Man to Call My Own novel. The data source is primary and secondary data source. The primary data source taken from A Man to Call My Own novel itself, by Johanna Lindsey and the secondary data source are about the biography novelist, some book, encyclopedias, website searching about Man to Call My Own novel and another data related to this study. The method used for collecting data is Library research and documentation. The technique of data analysis is descriptive analysis. Based on the analysis, the researcher concludes that the problem faced by the major character is anxiety in hatred her twins. In order to, the researcher used a psychoanalytic Approach such as id, ego, and superego. By using this method, it is know how Amanda Laton as major character can solve her problem that getting her live better. Based on the structural elements, the researcher concludes into two parts, the first is structural element and the second one is discussion. The research explains the element like: character and characterization, setting, plot, point of view, style and them.